Apparent rapid response to the combination of zolpidem, memantine and aripiprazole in a case of schizophrenic catatonia - Cruzado, Lizardo (2023)
Objective: The treatment of catatonia usually involves the use of benzodiazepines and, if these fail, electroconvulsive therapy is applied. Nevertheless, hypothetical neurobiological pathways involved in catatonia postulate beneficial effects of GABAergic drugs and glutamate blockers. Clinical case: A 45-year-old female patient, diagnosed with paranoid schizophrenia who developed a catatonic stupor (with no response to benzodiazepines) and various medical complications; however, the condition improved rapidly with the combination of zolpidem, memantine and aripiprazole. Result: A favorable outcome was obtained in this case, not achieved with the previous use of standard benzodiazepine therapy. Conclusions: The combination of GABAergic drugs and glutamate blockers can be beneficially implemented in cases of catatonic stupor that fail to respond to the usual management with benzodiazepines.